Measuring Students’ Perceptions of Quality Online Learning in the Era of COVID-19 – A Case Study of Students in the Accounting Department at Taif University – - Fallatah, Rasha Abdulrhman (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify students’ attitudes about distance learning in accounting courses. The study used a descriptive analysis approach, and a sample of 470 students from Taif University’s Accounting Department was selected. The results indicated that there was a positive relationship between students and their levels of satisfaction with distance learning due to their communication with each other and their teachers and the quality of education and its outcomes.